2022
DOI: 10.3389/fmolb.2022.892763
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mapping and Dynamics of Site-Specific Prolyl-Hydroxylation, Lysyl-Hydroxylation and Lysyl O-Glycosylation of Collagens Deposited in ECM During Zebrafish Heart Regeneration

Abstract: Cardiac fibrosis-mediated heart failure (HF) is one of the major forms of end-stage cardiovascular diseases (CVDs). Cardiac fibrosis is an adaptive response of the myocardium upon any insult/injury. Excessive deposition of collagen molecules in the extracellular matrix (ECM) is the hallmark of fibrosis. This fibrotic response initially protects the myocardium from ventricular rupture. Although in mammals this fibrotic response progresses towards scar-tissue formation leading to HF, some fishes and urodeles hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 55 publications
(104 reference statements)
0
19
0
Order By: Relevance
“…Analogously, our data identified that the protein level and phosphorylation on Ser1124 and Ser1247 of COL1A2 significantly decreased. Numerous PTMs occur in the biosynthesis of collagen molecules, including hydroxylation of proline and glycosylation of lysine [22]. However, there are few reports on the phosphorylation modification of collagen molecules, which suggests that it may be an overlooked but important research area.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, our data identified that the protein level and phosphorylation on Ser1124 and Ser1247 of COL1A2 significantly decreased. Numerous PTMs occur in the biosynthesis of collagen molecules, including hydroxylation of proline and glycosylation of lysine [22]. However, there are few reports on the phosphorylation modification of collagen molecules, which suggests that it may be an overlooked but important research area.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen biosynthesis involves heavy post-translational modifications (PTMs). Proteomics studies have shown that these PTMs have a role in the stability, function, and communication of collagen I with other ECM components and cell-surface receptors to regulate cell adhesion, migration, and cardiac regeneration ( Pokidysheva et al, 2014 ; Basak et al, 2016 ; Merl-Pham et al, 2019 ; Sarohi et al, 2022b ). Injury and scars are non-repairable in the mammalian heart due to a lack of regeneration capability ( Cutie and Huang, 2021 ).…”
Section: Extracellular Components Altered During Cardiac Fibrosismentioning
confidence: 99%
“…In an interesting proteomic study done by Sarohi et al, they detected 36 collagen chains in zebrafish heart. The levels of collagen PTMs were found to be altered during the regeneration process in the zebrafish heart ( Sarohi et al, 2022b ). This hints toward the role of collagen PTMs in the zebrafish heart-regeneration process.…”
Section: Extracellular Components Altered During Cardiac Fibrosismentioning
confidence: 99%
See 2 more Smart Citations